Exploring the implications of 'low visibility' specialist cyber-crime units. Issue 4 (December 2019) - Harkin, Diarmaid; Whelan, Chad
Using original data gathered within Australia, this paper argues that specialist cyber-policing units experience a pronounced level of low visibility within the police. This low visibility has three key dimensions. Firstly, there is low 'vertical' visibility as higher management and supervisors often have a limited understanding of the nature of the work and the needs of these units. Secondly, there is low 'horizontal' visibility as peers and colleagues within the wider organisation are similarly lacking in terms of their understanding of cyber-policing. The third dimension of low visibility concerns the external–internal visibility of the units as they relate to outside stakeholders including politics, media, the wider community and the judiciary. It is argued there is also a significant level of disinterest, disengagement and ignorance along this external–internal dimension. The implications of this 'low visibility' is explored and it is argued that there are consequences for the effectiveness of the units while also raising concerns around accountability and the overall prospects for progressive change.